Comparing human papillomavirus vaccine knowledge and intentions among parents of boys and girls. Issue 6 (2nd June 2016) - Lindley, Megan C.; Jeyarajah, Jenny; Yankey, David; Curtis, C. Robinette; Markowitz, Lauri E.; Stokley, Shannon
ABSTRACT: Background/Objective: Human papillomavirus (HPV) is the most common sexually transmitted infection in the United States. Previous research suggests some differences between male and female adolescents in correlates of vaccine receipt and reasons for non-vaccination; few studies examine both sexes together. This analysis assessed knowledge and attitudes related to HPV disease and vaccination, intention to vaccinate, and reasons for delayed vaccination or non-vaccination among parents of boys and girls 13–17 y old in 50 states, the District of Columbia, and selected local areas. Methods: National Immunization Survey-Teen 2013 data were analyzed and gender differences examined. Results: In this sample, adolescent boys were more likely than girls to be unvaccinated and less likely to have completed the HPV vaccination series (p < 0.005 for both). Parents of girls were more likely than parents of boys to report a provider recommendation for HPV vaccination (65.0% vs. 42.1%). Only 29% of girls' parents reported a provider recommendation to begin vaccination by 11–12 y old. Among unvaccinated teens, parental intention to vaccinate in the next 12 months did not differ by sex, but reasons for vaccination or non-vaccination did. Many parents do not know the recommended number of HPV doses. Conclusions: Gender differences in provider vaccination recommendations and reasons for vaccination might partially explain differential HPV uptake by male and female adolescents. Clinicians should offer strong recommendations for HPV vaccination at 11–12 y old for both girls and boys. To reduce missed opportunities, HPV vaccination should be presented in the context of, and given concurrently with, other routinely administered vaccines.